International Business English Program: Reflections on Design - Angela Bailey; Lourdes Rey; Nayibe Rosado (Universidad de La Sabana, 2009)
Designing a program is a long and difficult process, but the benefits and the personal growth of such an activity is impressive. In this paper the authors would like to reflect on decisions made throughout the program design of the International Business English Program at the Instituto de Idiomas of the Universidad del Norte. The authors will discuss considerations made during the design process, procedures implemented and changes experienced during the growth of the program. Finally, the authors will share how the experience has impacted their professional growth and continuous commitment to the International Business English Program and provide commentary as to why such a procedure albeit complicated is valuable for anyone.